Data collection protocol for wireless sensor network-based home automation - Ong, Arlyn Verina L. (Animo Repository, 2013)
Ambient intelligent home automation systems allow technologies to be installed within a home to automate several environment monitoring and control functions within a home, and to recognize the inhabitant including his or her affect and activities then respond accordingly. A requirement of such systems is to gather data from a multitude of different sensors each exhibiting different monitoring behavior. While wireless sensor networks (WSN) have been a popular platform to support such applications, these platforms are constrained by low bandwidth, and processing power. For these reasons, the traffic volume and data transmissions must be managed so that data may be delivered in a timely manner despite the limited resources. This study develops a data collection protocol that provides three data traffic priorities and uses a time division-based medium access control protocol to provide differentiated services to each traffic priority. When tested on a simulated model of an intelligent home, the protocol was able to exhibit data traffic prioritization, a high rate of data delivery and low latency.